2000
DOI: 10.1128/mcb.20.6.2098-2107.2000
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between the Drosophila Secreted Protein Argos and the Epidermal Growth Factor Receptor Inhibits Dimerization of the Receptor and Binding of Secreted Spitz to the Receptor

Abstract: Drosophila Argos (Aos), a secreted protein with an epidermal growth factor (EGF)-like domain, has been shown to inhibit the activation of the Drosophila EGF receptor (DER). However, it has not been determined whether Aos binds directly to DER or whether regulation of the DER activation occurs through some other mechanism. Using DER-expressing cells (DER/S2) and a recombinant DER extracellular domain-Fc fusion protein (DER-Fc), we have shown that Aos binds directly to the extracellular domain of DER with its ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2001
2001
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(23 citation statements)
references
References 71 publications
1
22
0
Order By: Relevance
“…Our studies suggest that Kek1 is functionally similar to another Drosophila suppressor of DER signalling called Argos. Argos is also a transcriptional target of activated DER in developing tissues (Golembo et al, 1996;Wasserman and Freeman, 1998), and it has been demonstrated that Argos binds directly to DER to inhibit the binding of the natural ligand Spitz (Jin et al, 2000). However, the sequences of the two inhibitors are very distinct.…”
Section: Mechanism Of Der/erbb Binding and Inhibitionmentioning
confidence: 99%
“…Our studies suggest that Kek1 is functionally similar to another Drosophila suppressor of DER signalling called Argos. Argos is also a transcriptional target of activated DER in developing tissues (Golembo et al, 1996;Wasserman and Freeman, 1998), and it has been demonstrated that Argos binds directly to DER to inhibit the binding of the natural ligand Spitz (Jin et al, 2000). However, the sequences of the two inhibitors are very distinct.…”
Section: Mechanism Of Der/erbb Binding and Inhibitionmentioning
confidence: 99%
“…The requirement of Argos as an inhibitory ligand of Egfr (Jin et al, 2000) and the identification of argos rlt suggested that Egfr signaling plays a critical role in ommatidial rotation. As Egfr is very pleiotropic with multiple requirements throughout development and eye patterning in particular (Bogdan and Klambt, 2001;Casci and Freeman, 1999;Freeman, 1997;Schweitzer and Shilo, 1997;Van Buskirk and Schupbach, 1999), it is not possible to analyze the role of Egfr in ommatidial rotation using mitotic clones of null alleles.…”
Section: Ommatidial Rotation Is Controlled By Egfr Signalingmentioning
confidence: 99%
“…The first, called Argos, contains an unconventional EGF-like domain that disrupts the spacing between cysteine residues found in the activating EGF-like ligands. Argos acts as an antagonist of fly EGF receptor activity (Jin et al, 2000;Vinos and Freeman, 2000), binding to the receptor with modest affinity and inhibiting activation by other ligands. Argos is expressed in response to EGF receptor activation, and is thought to contribute to receptor inhibition events critical for proper development (Stevens, 1998).…”
Section: Negative Modulator Proteinsmentioning
confidence: 99%